KNOWLEDGE-BASED LEADERSHIP AS A KEY FACTOR IN BUSINESS SUCCESS – CASE STUDY OF MONTENEGRO - Gordana Nikčević; Đorđije Pavićević (Agora International Journal of Economical Sciences)
In the contemporary globalized environment, effective leadership becomes a crucial factor for managing change and achieving sustainable business success. Leaders, through their knowledge, skills, and ability to manage knowledge, have a key role in shaping organizations that successfully adapt to dynamic market conditions. Continuous learning and application of knowledge enable leaders to respond to complex challenges of modern business. The aim of this research is to examine how leading principles, observed through knowledge management, influence the education of leaders in Montenegro and their readiness to face global challenges, as well as their contribution to achieving business success. The results indicate that leaders in Montenegro possess significant developmental potential, but also that, in addition, there is room for improvement, especially in the areas of leadership styles, knowledge sharing, readiness to take risks, and digital transformation. As directions for improvement, the need for adapting leadership to specific situations, greater openness and transparency, encouraging innovative thinking, development of multicultural competencies, and focus on international cooperation stand out.